From lanthanide chlorides to lanthanide pentafluorophenolates via lanthanide N, N-dialkylcarbamates. (8th January 2015) - Armelao, Lidia; Belli Dell'Amico, Daniela; Bottaro, Gregorio; Falvo, Paola; Labella, Luca; Marchetti, Fabio; Parisi, Daniela; Samaritani, Simona
Graphical abstract: A new method of synthesis of neodymium and terbium pentafluorophenolates, containing 1, 10-phenanthroline, [Ln(OC6 F5 )3 (phen)3 ] is described. The precursors are the lanthanide N, N -dibutylcarbamato complexes, [Ln(O2 CNBu2 )3 ], easily obtained from aqueous solutions of lanthanide salts. The crystal structures of [Nd(OC6 F5 )3 (phen)3 ] and [Tb(OC6 F5 )3 (phen)2 (H2 O)·phen] and photoluminescence spectra of the neodymium and terbium complexes are reported. Abstract: Neodymium and terbium pentafluorophenolates, containing 1, 10-phenanthroline as ancillary ligand, [Ln(OC6 F5 )3 (phen)3 ], (1 Ln = Nd, 2 Ln = Tb) have been synthesized by reacting the N, N -dibutylcarbamato complexes, [Ln(O2 CNBu2 )3 ], easily obtained from aqueous solutions of lanthanide salts, with C6 F5 OH in the presence of 1, 10-phenanthroline. The formation of the sparingly soluble hydrated compound [Tb(OC6 F5 )3 (phen)2 (H2 O)·phen], 3, was observed, due to fortuitous presence of water. Single crystal X-ray diffraction studies on compounds1, 3 and3 ·DME (DME = dimethoxyethane) showed coordination numbers (CN) 9 for neodymium in1 and 8 for terbium in3 and3 ·DME, where only two 1, 10-phenanthroline ligands are coordinated to terbium, the third forming two hydrogen bonds with the coordinated water. The structural characterisation of [NH2 Bu2 ][C6 F5 O], 4, showed the organisation of the product in ionic quartets. The photoluminescence spectra of1 and2 displayed the typical emissions related to the lanthanide centre in the NIR and visible region, respectively.